PENGARUH PEMBERIAN DOLOMIT DAN PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max (L.) Merr) DI TANAH ULTISOL - Nuraini, Putri; Budianta, Dedik; Siti Nurul Aidil , Fitri (Fakultas Pertanian Universitas Palangka Raya, 2021)
This research was conducted at the ATC Experimental Garden, Faculty of Agriculture, Sriwijaya University, Indralaya, Ogan Ilir Regency, and began in September 2019 until February 2020. The analyzes of soil and plant have been carried out at the Laboratory of Chemistry, Biology, and Soil Fertility, Soil Department, Faculty of Agriculture, Sriwijaya University, Indralaya. This study aims at determining the effect of dolomite and cow manure on the growth and production of soybean (Glycine max (L.) Merr) in Ultisol Soil. This study used a factorial randomized block design with 2 treatment factors and 3 replications. The first factor is dolomite CaMg (CO3)2 consisting of two levels, 5 tons ha-1 and 10 tons ha-1. The second treatment factor is cow manure consisting of three levels, namely without manure, 10 tons ha-1, and 20 tons ha-1. The results indicated that interaction the giving of dolomite and cow manure had a significant effect in increasing soil pH, and plant N uptake. The giving of dolomite 10 tons ha-1 significantly affected the weight of 100 seeds and soybean production The giving of cow manure 20 tons ha-1 had a very significant effect on plant height, total number of pods, and the number of filled pods of soybean in Ultisols.